Economic evaluation of an agroforestry system in hill zone of Karnataka - MUTANAL, S M; NADAGOUDAR, B S; PATIL, S J (The Indian Journal of Agricultural Sciences, 2014)
An experiment involving arable crops, viz rice (Oryza sativa L.), maize (Zea mays L), sunnhemp (Crotolaria juncea L.), silvicultural crops (E. tereticomis L.), C. equisetifolia J. R. & G. Foret, A. molucana (L.) Benth, T grandis L.) F., D.sissoo Roxb), horticultural crop (sapota) and pasture (grass Panicum maximum L.) was initiated in black clayey soils of Prabhunagar, Dharwad during 1976, Sapota (Achras sapota L.) was planted at 10 m apart and 3 trees were planted between 2 plants of sapota. Grass was planted in 1 m wide strip on either side of sapota + tree species. At the end of 17 years, trees were felled. Income from tres was higher in field crops + sapota with inclusion of teak and eucalyptus trees. Higher income from sapota was In sole crop and with A. molueana. Total average income from field crop + sapota + teak was higher by 46 % than with field crops + sapota. Net pay back value and benefit: cost ratio were higher in sapota+teak (Rs 1633 176 and 9.31 respectively) and sapota + sissoo (Rs 6754 08 and 4.34 respectively).